TINJAUAN HUKUM TERHADAP PERJANJIAN JUAL BELI TENAGA LISTRIK ANTARA PT. PLN (PERSERO) DENGAN PELANGGAN - DEWI LESTARI SIMANJUNTAK (PREMISE LAW JURNAL, 2013)
ABSTRACT The increasing number of population accompanied by facility and infrastructure development as well as the improvement in the field of business and economic activity require the increase of existing electric power as needed. The problem discussed in this study were how the electric power trading agreement was legally implemented between PT. PLN (State Electricity Company) and its customers, what attempts and sanctions were given by PT. PLN (Persero) to the customers who breached the electric power trading agreement, and what constraints were faced by PT. PLN (Persero) in overcoming the breach done by the customers. The constraints faced by PT. PLN (Persero) in overcoming the breach of law on electric power were limited operational cost, less clear official report writing, less complete work equipment brought, less rigorous officers, the people who dared to make their own electricity connection, the field workers with limited understanding of law, and others. Keywords: Legal Review, Trading, Electric Power